Study of the oxidation stability and exhaust emission analysis of Moringa olifera biodiesel in a multi-cylinder diesel engine with aromatic amine antioxidants. (August 2016) - Rashed, M.M.; Masjuki, H.H.; Kalam, M.A.; Alabdulkarem, Abdullah; Rahman, M.M.; Imdadul, H.K.; Rashedul, H.K.
Abstract: In this study, the two most effective aromatic amine antioxidants N, N′-diphenyl-1, 4-phenylenediamine (DPPD) and N-phenyl-1, 4-phenylenediamine (NPPD), were used at a concentration of 2000 ppm. The impact of antioxidants on the oxidation stability, exhaust emission and engine performance of a multi-cylinder diesel engine fuelled with MB20 (20% Moringa oil methyl ester and 80% diesel fuel blend) were analysed at varying speed conditions at an interval of 500 rpm and a constant load. It was observed that, blending with diesel enhanced the oxidation stability of the moringa biodiesel by approximately 6.97 h, and the addition of DPPD and NPPD to MB20 increased the oxidation stability up to 34.5 and 18.4 h, respectively. The results also showed that the DPPD- and NPPD-treated blends reduced the NOx emission by 7.4% and 3.04%, respectively, compared to the untreated blend. However, they do have higher carbon monoxide (CO) and hydrocarbon (HC) levels and smoke opacities, but it should be noted that these emissions are still well below the diesel fuel emission level. The results show that the addition of antioxidant with MB20 also improves the engine's performance characteristics. Based on this study, MB20 blends with amine antioxidants can be used in diesel engines without any modification. Highlights: DPPD, NPPD are the most promising antioxidant for improving oxidation stability. Treated MB20 reduced about 3.04–7.4% avg. NOx compared to untreated MB20. Treated blends produced higher HC, CO and smoke compared to untreated blends. MB20 with AO produced avg. 0.61–1.17% higher BP and 1.01–1.5% lower BSFC than MB20.